B. F. Skinner’s analysis of verbal behavior: a chronicle (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
A time line of Skinner’s work on verbal behavior must start at the very beginning of his scientific career. Skinner laid down the conceptual framework of his Theory of Behavior as early as his thesis. He developed his experimental work within this framework, and depended on research results to adjust and modify his theory. At the same time, he initiated efforts to interpret verbal behavior within his theoretical formulations and upon the operant relations he discovered in the laboratory. Work on both mediated and nonmediated relations entwined throughout his career. He discovered the basic verbal relations slowly and inductively over a twenty-five year span of effort.